2022
DOI: 10.1039/d2mh00281g
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastretchable, high-performance, and crosstalk-free proximity and pressure bimodal sensor based on ionic hydrogel fibers for human-machine interfaces

Abstract: The traditional human-machine interaction mode of communicating solely with pressure sensors needs modification, especially at a time when COVID-19 is circulating globally. Here, a transparent, stretchable, resilient, and high-performance hydrogel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 46 publications
0
64
0
Order By: Relevance
“…26 Furthermore, ion-conducting hydrogels can electrically respond to various stimuli such as temperature, humidity, ion, strain and pressure, etc., showing great application potential in wearable electronics. [27][28][29][30][31][32][33] At present, concentrated endeavor has been devoted to constructing hydrogel-based flexible strain/pressure sensors for real-time monitoring of human motion and biological signals, but the research on ion-conducting hydrogel-based stretchable NO 2 gas sensors is relatively infrequent. [34][35][36][37] Wu et al first reported a stretchable polyacrylamide (PAM)/carrageenan DN hydrogel-based NO 2 sensor with an air background.…”
Section: Materials Horizonsmentioning
confidence: 99%
“…26 Furthermore, ion-conducting hydrogels can electrically respond to various stimuli such as temperature, humidity, ion, strain and pressure, etc., showing great application potential in wearable electronics. [27][28][29][30][31][32][33] At present, concentrated endeavor has been devoted to constructing hydrogel-based flexible strain/pressure sensors for real-time monitoring of human motion and biological signals, but the research on ion-conducting hydrogel-based stretchable NO 2 gas sensors is relatively infrequent. [34][35][36][37] Wu et al first reported a stretchable polyacrylamide (PAM)/carrageenan DN hydrogel-based NO 2 sensor with an air background.…”
Section: Materials Horizonsmentioning
confidence: 99%
“…Recently, hydrogels consisting of three-dimensional networks and numerous water molecules have emerged as a promising stretchable material for the fabrication of wearable electronics, thanks to its intrinsic stretchability and ionic conductivity [35][36][37][38][39][40][41]. Attractively, the ionic conductivity of hydrogels is directly related to their water content, and the adsorption and desorption of water molecules will inevitably cause its variation.…”
Section: Introductionmentioning
confidence: 99%
“…26 For instance, Ding et al fabricated an ionic hydrogel fiber-based sensor featuring crosstalk-free detection of proximity and pressure for human–machine interfaces. 27 Wu et al prepared a novel ionic hydrogel with good freezing and drying tolerances for high-performance temperature and strain sensing. 28 Liang et al developed an organohydrogel-based stretchable oxygen sensor, which can work under relatively extreme environmental conditions.…”
Section: Introductionmentioning
confidence: 99%